Can Psychological Expectation Models Be Adapted for Placebo Research? - Rief, Winfried; Petrie, Keith J. (Frontiers in Psychology, 2016)
Placebo responses contribute substantially to the effect and clinical outcome of medical treatments. Patients’ expectations have been identified as one of the major mechanisms contributing to placebo effects. However, to date a general theoretical framework to better understand how patient expectations interact with features of medical treatment has not been developed. In this paper we outline an expectation model that can be used as framework for experimental studies on both placebo and nocebo mechanisms. This model is based on psychological concepts of expectation development, expectation maintenance, and expectation change within the typical paradigms used in placebo research. This theoretical framework reflects the dynamic aspects of the interaction between expectations and medical treatment, and offers a platform to combine psychological and neurophysiological research activities.. Moreover, this model can be used to identify important future research questions. For example, we argue that the dynamic processes of expectation maintenance versus expectation changes are not sufficiently addressed in current research on placebo mechanisms. Therefore, the question about how to change and optimize patients’ expectations prior to treatment should be a special focus of future clinical research.